PENGARUH SEKTOR PERBANKAN SYARIAH DAN PASAR MODAL SYARIAH TERHADAP FINANCIAL DEEPENING DI INDONESIA - Ami Latifah; Arief Fitrijanto (Universitas Muhammadiyah Prof Dr Hamka, 2016)
This study aimed to analyze the factors that affect financial deepening in Indonesia. The variables used in this study is a Third Party Fund (DPK), Islamic Financing, Corporate Bonds, Sukuk to Financial Deepening in Indonesia. Analyses were performed using monthly time series data published by Bank Indonesia in the study period from January 2011 to December 2015.The analytical method used in this research is Ordinary Least Square (OLS). The resulting regression model showed that the variables Third Party Fund (DPK), Islamic Financing, Sukuk, Sukuk Corporation together have an influence on Financial Deepening in Indonesia. Partial, this research supports the Third Party Funds (TPF) positive and significant impact on the Financial Deepening, whereas in Islamic Financing does not affect the Financial Deepening. In addition the results of this study showed Corporate Sukuk and significant negative effect on the Financial Deepening, and for Sukuk which means partially positive and significant impact on the Financial Deepening in Indonesia.